KOMUNIKASI DATA PADA SISTEM PELAPORAN KECELAKAAN PERAHU NELAYAN BERBASIS LORA - Padriyana, Fadli; Nusuwars, Firmansyah M S; Hiron, Nurul (Journal of Energy and Electrical Engineering, 2021)
The job of being a fisherman is very risky, many factors that become the threat of work lurking a fisherman. Traditional fishermen are not facilitated with communication equipment that can support the safety of fishermen. So when something happens that can harm the fishermen, it can not be handled immediately. In this research developed a wireless communication system based on LoRa to be able to monitor fishermen working at sea by online,consisting of node devices attached to boats and  gateways that function to forward data from  the node device  to the web server using the MQTTprotocol, so that boat data can be monitored through  the  thingsboard dashboard. Data monitored include the location of fishing boats ( longitude  and  latitude coordinates ),the slope of the fishing boat (degree of roll and pitch) and also early warning. Testing the reliability of LoRa communication in marine communication scenarios is carried out by testing the distance of data transmission, data length and data delivery speed setting / air data rate with Line of Sight  (LOS) condition at Sea directly. From the results of data transmission reliability testing using the communication module LoRa E32 915T20D is able to reach the furthest distance up to 2.4 Km with the data send speed setting at 0.3 kbps  with an average delivery time delay  / time on air that tends to increase with the increase in the length of data sent.